2000
DOI: 10.1038/35020060
|View full text |Cite
|
Sign up to set email alerts
|

Diversity peaks at intermediate productivity in a laboratory microcosm

Abstract: The species diversity of natural communities is often strongly related to their productivity. The pattern of this relationship seems to vary: diversity is known to increase monotonically with productivity, to decrease monotonically with productivity, and to be unimodally related to productivity, with maximum diversity occurring at intermediate levels of productivity. The mechanism underlying these patterns remains obscure, although many possibilities have been suggested. Here we outline a simple mechanism--inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
219
2
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 293 publications
(239 citation statements)
references
References 24 publications
17
219
2
1
Order By: Relevance
“…This result was consistent with the findings by Kassen et al [15], Yang et al [16] and Wang et al [3] who observed that the higher species diversity, richness and evenness occurred in the middle level of productivities. On the one hand, the nutrient availability was usually higher at the lower altitude, which made a few species so robust and thus the less competitive species were excluded [4].…”
Section: Relationship Of Species Diversity With Aboveground Biomasssupporting
confidence: 83%
“…This result was consistent with the findings by Kassen et al [15], Yang et al [16] and Wang et al [3] who observed that the higher species diversity, richness and evenness occurred in the middle level of productivities. On the one hand, the nutrient availability was usually higher at the lower altitude, which made a few species so robust and thus the less competitive species were excluded [4].…”
Section: Relationship Of Species Diversity With Aboveground Biomasssupporting
confidence: 83%
“…This confirms expectations of both neutral theory and adaptive speciation. This is the second such experimental demonstration in a well-mixed enviornment of which we are aware (Figure 4a in Kassen et al 2000) and provides important unambiguous confirmation of this result in a different model system, over a longer time period. This is important because the role of spatial heterogeneity in generating biodiversity patterns has a long and distinguished history (Hedrick et al 1976;Tilman 1982;Hedrick 1986), and many hypotheses for natural diversity patterns rely on a significant role of spatial heterogeneity.…”
Section: Discussionmentioning
confidence: 66%
“…E. coli heterozygosity increased over time (Figure 1), and to a much higher degree in higher resource concentrations (day 3 concentration: F 36,125 ¼ 5.73, P , 0.0001). This strong and consistent response is only the second such monotonic diversification-resource-concentration relation of which we are aware (Kassen et al 2000). Number of different phenotypes also showed this pattern, although it is a less sensitive measure of changing phenotype frequencies (data not shown).…”
Section: Resultsmentioning
confidence: 92%
“…Ant assemblages across a large gradient of energy availability (NPP) in the Americas exhibit a positive species-energy relationship in which specialist detritivore species only occur in the very high-energy areas (Kaspari, 2001). The niche position mechanism may be closely related to the habitat heterogeneity mechanism, thus some support for the former is provided by studies demonstrating positive influences of habitat heterogeneity and food resource diversity on species richness in experimental microcosms (Kassen et al, 2000), fish (Eadie & Keast, 1984), birds (Hurlbert & Haskell, 2003) and mammals (Fox & Fox, 2000 ;Heaney, 2001). The role of energy availability in driving increased resource diversity, however, needs further investigation.…”
Section: ( C ) Evaluationmentioning
confidence: 99%